CXCR4/CXCL12 axis promotes lymphatic metastasis in tongue squamous cell carcinoma via PI3K/AKT signaling pathway - Huiquan Lou; Yichao Xia; Shengjie Shao; Xiang Liu; Zengzheng Li; Hongbin Yu; Yongsheng Li (Journal of Translational Medicine)
Abstract Background Given that lymphatic metastasis represents a pivotal determinant of poor clinical outcomes in tongue squamous cell carcinoma (TSCC), this study aimed to elucidate the role of the CXCR4/CXCL12 chemokine axis in TSCC lymphatic metastasis and its clinical significance. Methods We examined CXCR4 and CXCL12 expression in 87 TSCC specimens by immunohistochemistry and analyzed their correlation with clinicopathological features. TSCC cell lines with stable CXCR4 overexpression or knockdown were established to investigate cellular functions through proliferation, migration, invasion, and apoptosis assays. Mechanistic studies were conducted using pharmacological inhibitors, western blotting, and lymphatic endothelial cell functional assays. An orthotopic TSCC mouse model was developed to validate findings in vivo. RNA sequencing was performed to analyze global transcriptomic changes. Results CXCR4 and CXCL12 were significantly upregulated in TSCC tissues compared to adjacent normal tissues, with expression levels correlating with lymph node metastasis and poor survival. CXCR4 overexpression enhanced TSCC cell proliferation, migration, invasion, and epithelial-mesenchymal transition while suppressing apoptosis. Mechanistically, CXCL12 activated the PI3K/AKT pathway in a time- and dose-dependent manner, and pathway inhibition using AMD3100 or LY294002 attenuated pro-metastatic phenotypes. CXCR4/CXCL12 signaling promoted lymphangiogenesis by enhancing lymphatic endothelial cell proliferation, migration, and tube formation. In vivo, CXCR4 overexpression accelerated tumor growth and lymphatic metastasis, while CXCR4 inhibition showed opposite effects. Transcriptomic analysis revealed comprehensive molecular alterations regulated by CXCR4/CXCL12 signaling. Conclusions The CXCR4/CXCL12 axis functions as a crucial mediator of TSCC lymphatic metastasis by promoting tumor cell invasiveness and lymphangiogenesis via the PI3K/AKT pathway. CXCR4 and CXCL12 serve as independent prognostic biomarkers for TSCC lymphatic metastasis and represent promising therapeutic targets for this aggressive malignancy. Graphical Abstract